The The Effectiveness of TPACK and PWIM Learning Models in Improving Arabic Learning Outcomes for Eighth-Grade Students at MTsN 3 Sragen Academic Year 2025/2026 - Ratna Ayu; Alif Cahya Setiyadi (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
In the era of digital transformation, innovation in learning methodologies has become a crucial aspect for Islamic educational institutions like MTsN 3 Sragen to maintain instructional quality. However, issues regarding low Arabic learning outcomes among 8th-grade students persist, driven by a reliance on traditional methods and diverse educational backgrounds. This study compares the effectiveness of the TPACK and PWIM models against traditional methods in enhancing learning achievement. Employing a quantitative Quasi-Experimental approach with One-Way ANOVA and N-Gain Score analysis, the results demonstrate that the TPACK model is the most effective, achieving an N-Gain score of 75.98%, surpassing PWIM (60.9%) and traditional methods (38.49%). Consequently, technology integration through TPACK serves as a strategic solution to enhance the efficiency of Arabic language learning in madrasahs.